Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Mitra Sakti Boshe VVIP Club Yogyakarta - Luthfi Umamul Husna; Bangun Putra Prasetya (Pusat Riset dan Inovasi Nasional, 2024)
Factors that influence employee performance include motivation and work environment. This research aims to find out whether motivation and work environment influence employee performance at PT. Mitra Sakti Boshe VVIP Club Yogyakarta. This type of research is included in quantitative research. This research was conducted at the company PT MITRA SAKTI BOSHE VVIP CLUB YOGYAKARTA. The population in this study were 20 employees at BOSHE VVIP CLUB YOGYAKARTA. The sampling technique used in this research is saturated sampling. In data collection carried out using primary data, primary data is by distributing questionnaires to respondents. The data collection technique in this research is a questionnaire. This research was analyzed using multiple linear regression using the IBM SPSS Statistics 26 program. Variable measurements used a Likert Scale: Strongly Agree (weight 5), Agree (weight 4), Neutral (weight 3), Disagree (weight 2) and Strongly Disagree (weight 1). The analytical tools used in this research are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test: T test and F test. It is hoped that the results of this research will serve as a basic reference later in making a thesis proposal, So this research method will also study procedures regarding motivation and work environment on employee performance. Research and includes activity steps, as well as research methods that will later be used.